The Pragmatics Of Swahili Relative Clauses - Mwamzandi, Mohamed (My University, 2022)
Several studies explain the variation of the Swahili relative clause (RC) from a syntactic perspective. These studies discuss the derivational and structural differences/similarities between the amba RC and the tensed RC. In this study, the choice between the amba and tensed RCs is explained from a pragmatic perspective. 440 RCs were extracted from the Helsinki Corpus of Swahili. The dataset was then coded for various variables including relative marker (amba/tensed), relative type (restrictive/non-restrictive), length (number of words used), and information status (topic/non-topic). The results show that the tensed RCs are mostly restrictive while the amba RCs are mostly non-restrictive. Further, the mean length of the amba RC is higher than of the tensed RC. It was observed that the amba RC is preferred in topic shift transition, that is, when a non-topic NP becomes the topic NP in the following utterance while the tensed RC is preferred in continue transition, that is, if the topic of the matrix clause is the same as that of the RC.
Keywords: Swahili relative clauses; Amba relative clause; Tense Relative clause